Experiences of patients living with HIV and AIDS on antiretroviral therapy in Accra, Ghana - Joana Agyeman-Yeboah; Esmeralda J. Ricks; Margaret Williams; Portia J. Jordan (AOSIS, 2024)
Background: The human immunodeficiency virus and acquired immunodeficiency syndrome (HIV and AIDS) pandemic has greatly affected Africa, particularly Ghana. The pandemic remains a public health concern, particularly in terms of accessing essential medication and improving quality of life for people living with the disease. Objectives: This study aimed to explore and describe the experiences of persons diagnosed and living with HIV who are on antiretroviral therapy. Method: A qualitative, exploratory, descriptive, and contextual design was used. The research population included persons diagnosed with HIV who were receiving antiretroviral therapy at three public hospitals in Ghana. Data saturation was achieved after conducting 15 semi-structured interviews. Creswell's six steps of data analysis were used to analyse the data, which resulted in the emergence of one main theme and six sub-themes. Results: The main theme identified by the researchers highlighted the participants' diverse experiences of being diagnosed and living with HIV. It was found that the study participants expressed shock, disbelief, surprise, and fear of death after being diagnosed with HIV. The participants also experienced stigmatisation, discrimination, and rejection. Conclusion: There is a need for further research on the extent of discrimination and stigmatisation and the effect on optimal adherence to antiretroviral therapy. Continuous public education on HIV is required to limit the extent of discrimination and stigmatisation. Contribution: The study has highlighted the various emotions related to stigma and discrimination expressed by persons living with HIV (PLHIV). The findings will guide policy on eliminating discrimination and stigmatisation for people living with HIV.